PB.04 Nursing the Surgical Neonate – Developing a Course to Support Regional Requirements in the West Midlands. (9th June 2014) - Reda, B; Philpott, A; Dudley, A; Stretton, J
Abstract : Historically, in the West Midlands the demand for neonatal surgical cots outweighed the capacity of the regional Children's Hospital (Birmingham Children's Hospital (BCH)). This led to babies being transferred outside the local region to receive surgical care. In 2008 a surgical project was implemented to enable services to provide for the needs of the local population. New pathways were developed to return surgical neonates to referring units at an earlier stage in their recovery, freeing surgical cots at BCH. Course development: A course was developed to enhance skills and knowledge for neonatal nurses and paediatric nurses working on a neonatal surgical ward, in keeping with DoH guidance for neonates with surgical conditions. 1 A multi-disciplinary faculty was involved in module development; it was supported by BCH and the Southern West Midlands Newborn network (SWMNN); accreditation is by Stafford University at 30 credits (level 6). Course design: 10 study days including a poster presentation 3 week placement on a dedicated neonatal surgical ward Clinical practice in own setting Protected self-directed study Assignments Competency booklet. Results: Two cohorts of students have completed the course (14 students), from 4 units. Feedback has been positive, with the majority of students commenting on the usefulness of the surgical placement and importance for their own unit. Conclusion: The surgical module is an essential regional resource which is recruiting to the 3rd cohort in April 14. The module was designed to ensure neonates are cared for in the most appropriate location whilst facilitating early return to referring units. Reference: Department of Health (2009) Toolkit for High-Quality Neonatal Services www.dh.gov.uk/en/DH_107845